EXPERIENCING THE PAST: THE APPLICABLE VIEWS OF HISTORY TEACHERS TOWARDS HISTORICAL REENACTMENT IN HISTORY LESSON - Neval AKÇA BERK (International Journal of Eurasia Social Sciences, 2017)
The aim of this study is to reveal the views of history teachers towards historical reenactment applied as a method. In this research designed according to the general scaning model, the data have obtained from questionnaire applied to determine the thoughts of the 100 history teachers who participated in the introduction meeting of the project titled.. “TALOK-O Project: The Use and Effectiveness of Historical Reenactment in Order to Reveal the Perception of History of Secondary School”. The findings obtained are presented as percentage and frequency. In this study, it has been determined that history teachers expressed their dramatization methods which they apply in classes or visits to historical places as experiences of historical reenactment. Examining the relevant literature, it is possible to state that these practices which history teachers had, are not actually the historical reenactment and they have no experience about this. The history teachers have pointed out that the historical reenactment is seen as an effective and feasible method for history lessons, but they have limitations such as inadequacy (in terms of school, class, economy, tools, equipment), limitation of teaching hours, and the necessity of teaching program. The history teachers have stated that according to them the periods of Ottoman, National Struggle, Ancient and Central Asian Turkish History; the subjects about military, socio-cultural life and local history; the events such as the War of Independence and the Conquest of Istanbul are suitable for historical reenactment at a high level. The history teachers have not seen the political issues applicable as other issues at the same level for historical reenactment. Thinking the many history teachers as the teachers who have 16 years or more of experience, saying that history teachers can provide an effective learning environment for historical reenactment and seeing that historical reenactment is feasible; it is meaningful that they have avoid to apply such studies due to their limitations and express that they do not know how to apply it.